The trouble with self-determination: Canada, Soviet colonialism and the United Nations, 1960–1963. Issue 3 (2nd April 2016) - McKercher, Asa
Abstract : In 1960, Canadian Prime Minister John Diefenbaker embarked on a campaign to see the United Nations (UN) recognise and censure Soviet colonialism. This effort is often cited as an example of Diefenbaker's populism and his pandering to ethnic voters. But to the prime minister, it was unconscionable that, with Eastern Europe under Moscow's thumb, the UN should direct its opprobrium entirely towards Britain, France, and other colonial powers then in a process of imperial devolution. Ultimately more than a mere quixotic reflection of populist pandering, Diefenbaker's campaign to secure a UN condemnation of the Soviet Union was a nascent but imperfect effort to inject the promotion of human rights into Canada's foreign policy at a point where self-determination was a significant area of international contestation. This initiative raised valid questions about the commitment of anti-colonial powers to universal self-determination thereby showcasing the ambiguities extant in the effort by the anti-colonial movement as it employed human rights.